THE CORRELATION BETWEEN INTRAPERSONAL INTELLIGENCE WITH STUDENT ACADEMIC ACHIEVEMENT IN BIOLOGY - Jihan Nuraini; Ade Suryanda; Nurmasari Sartono (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2019)
ABSTRACTEducation is a means of gaining knowledge to improve the quality of human resources in global competition. Therefore, improving the quality of education is needed through schools as formal institutions. As a formal institution, the school can provide provisions for students to achieve success in the learning process which is reflected in academic achievement, one of them is in biology learning. This study aimed to determine the correlation between intrapersonal intelligence (X) with student academic achievement in biology (Y). Research conducted at SMA Negeri 4 Bekasi Utara in April 2019. The method used is correlational. Data were analyzed with bivariate correlation coefficient significance test. The results showed that there was a significant positive correlation (r= 0,260) between Xwith Y through linear regression equation Ŷ = 71,407 + 0,084X. Keywords: biology learning, intrapersonal intelligence, student academic achievement.